Postweaning Isolation Rearing Alters the Adult Social, Sexual Preference and Mating Behaviors of Male CD-1 Mice - Liu, Zi-Wei; Yu, Yu; Lu, Cong; Jiang, Ning; Wang, Xiao-Ping; Xiao, Shui-Yuan; Liu, Xin-Min (Frontiers in Behavioral Neuroscience, 2019)
Objective: No study has comprehensively evaluated the effect of postweaning isolation on the social and sexual behaviours of a certain strain of rodents in ethology. The present study aims to explore how and to what extent isolation rearing after postweaning affects the social and sexual behaviours of male CD-1 mice in adulthood systematically. Methods: Male CD-1 mice were randomly assigned to two groups: isolation reared (IS, one mouse per cage, n = 30) and group housed (GH, five mice per cage, n = 15). The mice underwent isolation rearing from postnatal day 23 to day 93. Then, social affiliation, recognition and memory were measured through selection task experiments. Social interaction under a home cage and novel environment were measured via resident-intruder and social interaction test, respectively. Furthermore, sexual preference, homosexual and heterosexual behaviours were measured. Results: Our study found that postweaning isolation increased the social affiliation for conspecifics (p = 0.001), reduced social recognition (p = 0.042) and impaired social memory. As for social interaction, isolated mice showed a remarkedly increased aggression towards the intruder male in a home cage or novelty environment. For instance, isolated mice presented a short attack latency (p < 0.001), high attack frequency (p < 0.001) and long attack duration (p < 0.001). In addition, isolated mice exhibited further social avoidance. Contrastingly, isolated mice displayed a reduced sexual preference for female (IS: 61.47±13.80%, GH: 70.33±10.06%, p = 0.038). As for heterosexual behaviour, isolated mice have a short mating duration (p = 0.002), long mounting latency (p = 0.002) and long intromission latency (p = 0.015). However, no association was observed between postweaning isolation and homosexual behaviour in male CD-1 mouse. Conclusion: Postweaning isolation increased the social affiliation, impaired the social cognition and considerably increased the aggression in social interaction of adult male CD-1 mice. Postweaning isolation induced a decreased sexual preference for female in adulthood. Postweaning isolation extended the latency to mate, thereby reducing mating behaviour. No association was observed between isolation and homosexual behaviour.